(untitled) (Journal of Information Technologies in Education (ITE), 2012)
The essence and didactic capabilities of laboratory works have been analyzed. Current state of their usage while training professional ecologists at the Khmelnytskyi National University has been considered. It has been found out that fulfilling of virtual laboratory works in combination with studying of real equipment, natural phenomena and processes improves level of knowledge, skills and abilities of students.